Alzheimer's Association Project VITAL: A Florida Statewide Initiative Using Technology to Impact Social Isolation and Well-Being - Prophater, Lorna E.; Fazio, Sam; Nguyen, Lydia T.; Hueluer, Gizem; Peterson, Lindsay J.; Sherwin, Kasia; Shatzer, Julie; Branham, Michelle; Kavalec, Amy; O'Hern, Karen; Stoglin, Kristi; Tate, Rio; et al. (Frontiers in Public Health, 2021)
Lack of social engagement and the resulting social isolation can have negative impacts on health and well-being, especially in senior care communities and for those living with dementia. Project VITAL leverages technology and community resources to create a network for connection, engagement, education, and support of individuals with dementia and their caregivers, and explores the impact of these interventions in reducing feelings of social isolation and increasing mood among residents during the COVID-19 pandemic. Through two phases, 600 personalized Wi-Fi-enabled iN2L tablets were distributed to 300 senior care communities (55% assisted living communities, 37% skilled nursing communities, 6% memory care communities, and 2% adult family-care homes) to connect and engage residents and their families. Different phases also included Project ECHO, a video-based learning platform, Alzheimer's Association virtual and online education and support for family caregivers, evidence-based online professional dementia care staff training and certification, and Virtual Forums designed to explore ways to build sustainable, scalable models to ensure access to support and decrease social isolation in the future. Tablet usage was collected over an 11-month period and an interim survey was designed to assess the effectiveness of the tablets, in preventing social isolation and increasing mood among residents during the COVID-19 pandemic. A total of 105 care community staff (whose community used the tablets) completed the survey and overall, these staff showed a high level of agreement to statements indicating that residents struggled with loneliness and mood, and that the tablet was useful in improving loneliness and mood in residents and allowing them to stay in touch with family and friends. Additional positive results were seen through a variety of other responses around the tablets and Project ECHO. Overall, the tablets were shown to be an effective way to engage residents and connect them with friends and family, as well as being a useful tool for staff members. A third phase is currently underway in the homes of people with dementia and their family caregivers, which includes tablets and direct access to Alzheimer's Association virtual and online education and support programs.